AB0003 A galnt3 gene mutation in two sibs with chronic recurrent multifocal osteomyelitis associated with hyperphosphatemic familial tumoral calcinosis. (12th June 2018) - El Dessouki, D.; Abdel-Hamid, M.S.; Mehrez, M.I.; Aglan, M.S.; Temtamy, S.A.
Abstract : Background: Chronic recurrent multifocal osteomyelitis (CRMO) is an uncommon inflammatory disease mostly affects the metaphyses of long bones. It can be distinguished from osteomyelitis by multifocality and recurrence. Hyperphosphatemic familial tumoral calcinosis (HFTC) is a rare genetic disorder characterised by increased re-absorption of phosphate through the renal proximal tubule leading to increased phosphate concentration and deposition of calcified deposits in cutaneous and subcutaneous tissues, as well as some visceral organs. HFTC is inherited in an autosomal recessive manner and is caused by mutations in three different genes, FGF23, GALNT3 and KLOTHO. CRMO has been associated with some chronic inflammatory diseases such as inflammatory bowel disease, palmoplantar pustulosis and SAPHO syndrome. The association of CRMO and HFTC is extremely rare and only three patients have been described so far in the literature. Objectives: To report the clinical, radiological and molecular findings of two sibs with CRMO associated with HFTC. Methods: In this report, we present two siblings; offspring of consanguineous parents. They presented with spontaneous bony pains not responding to NSAID and later on, that developed tender hard masses. There were no similarly affected family members, and they had a non-affected sibling. Clinical, laboratory, pathological and radiological examination was performed. Mutational analyses of the FGF23, GALNT3 and KLOTHO genes was carried out by Sanger sequencing of the entire coding region of each gene. Results: Laboratory results including blood cultures and sensitivities were normal, apart from mildly elevated ESR. Serum calcium, 25(OH) vitamin D, renal functions, albumin, alkaline phosphatase, parathormone hormone, and phosphorous were normal apart from hyperphoshatemia in both siblings. Initial x-rays revealed lytic lesions with a sclerotic margin. Follow up x-rays showed healing with sclerosis and hyperostosis. After developing the hard masses, x-rays showed calcified masses. Resection pathological analysis revealed non-neoplastic inflammatory bone growth with prominent periosteal and bone proliferation, it was free from any granulomatous or malignant changes. We suggested a provisional diagnosis of CRMO associated with HFTC. Molecular studies confirmed the diagnosis by identifying a known pathogenic mutation in the donor splice site of exon 8 of the GALNT3 gene, c.1524+1G>A. The mutation was found in the homozygous form in the two sibs and both parents were heterozygous. Conclusions: This study documents the first Egyptian family clinically diagnosed with CRMO associated with HFTC and confirmed by molecular studies, with the identification of a splice mutation in the GALNT3 gene. Acknowledgements: This work was funded by the STDF grant number 5253. Disclosure of Interest: None declared